2019
DOI: 10.14710/jksa.22.5.179-183
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Daemonorops draco Resin

Abstract: Jernang resin is secretion of jernang rattan (Daemonorops draco, Arecaceae family) fruits which is endemic in Southeast Asia. This resin has various biological activities and empirically used as wound healing, headache medicines, and fever remedies by Anak Dalam ethnic group from Jambi. This study was performed to evaluate the antioxidant activity of nonpolar fraction of D. draco resin which collected from Jambi Province, Sumatera, Indonesia. Resin was extracted with n-hexane, ethyl acetate, and methanol respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
7
0
2
Order By: Relevance
“…This indicates that the increasing polarity of the solvent (more water) does not increase the compound's solubility from the resin to the solvent. However, previous studies have shown that the yield produced from an extraction with nonpolar solvents (n-hexane) produces a very small yield, while the highest yield was obtained in an extraction with ethyl acetate [11]. Other studies also showed that a higher ethanol composition increased the extract yield of propolis, which was dominated by resin [17].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This indicates that the increasing polarity of the solvent (more water) does not increase the compound's solubility from the resin to the solvent. However, previous studies have shown that the yield produced from an extraction with nonpolar solvents (n-hexane) produces a very small yield, while the highest yield was obtained in an extraction with ethyl acetate [11]. Other studies also showed that a higher ethanol composition increased the extract yield of propolis, which was dominated by resin [17].…”
Section: Discussionmentioning
confidence: 95%
“…In a previous report using D. draco resin, the antioxidant activity of the ethyl acetate extract was relatively high, with a half-maximal inhibitory concentration (IC 50 ) of 27.61 µg/mL [11]. Moreover, the methanol extract of D. draco resin from Sarolangun (Jambi, Indonesia) has antioxidant content with an IC 50 value of 117.63 ± 3.02 µg/mL [12].…”
Section: Introductionmentioning
confidence: 95%
“…The solution was incubated for 30 minutes at room temperature. The absorbance of the solution was measured at a wavelength of 517 nm using a multi-well plate reader [ 19 ]. The positive control used was ascorbic acid.…”
Section: Determination Of Antioxidant Activity Of Dpph Methodsmentioning
confidence: 99%
“…Selain itu, getah jernang juga banyak digunakan untuk bahan baku pembuatan dupa. Di industri kesehatan, getah jernang banyak digunakan sebagai bahan obatobatan seperti obat disentri, diare, asma, obat untuk penyembuhan luka pada kulit (Jiang et al, 2017;; Namjoyan, Kiashi, Moosavi, Saffari, & Makhmalzadeh, 2016), obat untuk meningkatkan libido (aphrodisiac), bahan pasta gigi, anti bakteri, antifungal dan krem kulit antiageing (Gupta, Bleakley, & Gupta, 2007;; Jura-Morawiec, & Tulik, 2016) dan juga sebagai antioksidan (Purwanti, Wahyuni, & Batubara, 2019). Gambar 1.…”
Section: Pendahahuluanunclassified